2022
DOI: 10.1186/s12866-022-02580-4
|View full text |Cite|
|
Sign up to set email alerts
|

Community composition, bacterial symbionts, antibacterial and antioxidant activities of honeybee-associated fungi

Abstract: Background Fungi associated with insects represent one potentially rich source for the discovery of novel metabolites. However, a comprehensive understanding of the fungal communities of Apis mellifera ligustica remains elusive. Results Here, we investigated the phylogenetic diversity and community composition of honeybee-associated fungi using combination of culture-dependent and culture-independent approaches. A total of forty-five fungi were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
(72 reference statements)
0
10
1
Order By: Relevance
“…The relative abundances of ASVs showed data similar to ours at the phylum level, with a highest abundance of Ascomycota followed by a lower proportion of Basidiomycota. Data at genus level (Cui et al, 2022b) showed a relative abundance of Kodamaea higher than 80%, different from our results that recorded this genus at 8%, on the other hand, Metschnikowia was not detected at all (threshold 0.1%). The Metschnikowia genus was, on the contrary, detected at 18% of relative abundance in honeycomb in the same study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The relative abundances of ASVs showed data similar to ours at the phylum level, with a highest abundance of Ascomycota followed by a lower proportion of Basidiomycota. Data at genus level (Cui et al, 2022b) showed a relative abundance of Kodamaea higher than 80%, different from our results that recorded this genus at 8%, on the other hand, Metschnikowia was not detected at all (threshold 0.1%). The Metschnikowia genus was, on the contrary, detected at 18% of relative abundance in honeycomb in the same study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no isolation of the species detected in our work has been documented so far. A recent work by Cui et al (2022b) explored the phylogenetic diversity and community composition of A. mellifera ligustica associated fungi in honey bees and the colony environment, including the gut and bee-derived products using a combination of culture-dependent and cultureindependent approaches. The relative abundances of ASVs showed data similar to ours at the phylum level, with a highest abundance of Ascomycota followed by a lower proportion of Basidiomycota.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to containing a large number of gut bacteria, the bee gut is rich in fungi, which have antibacterial and antioxidant activities, and probiotic potential ( Hsu et al, 2021 ; Cui et al, 2022 ; Rutkowski et al, 2022 ). However, the effects of pesticide exposure on the gut fungi of bees are often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reaction was carried out with 15 μl of Phusion ® High-Fidelity PCR Master Mix (New England Biolabs), 2 μM of forward/reverse primers, and about 10 ng of template DNA. The reaction conditions of PCR were performed as described method (Cui et al, 2022). Mixture PCR products were purified with Qiagen Gel Extraction Kit (Qiagen, Germany).…”
Section: Culture-independent Community Analysismentioning
confidence: 99%